PENANGGULANGAN MASALAH BANJIR DAN PENGOLAHAN SAMPAH MANDIRI DENGAN METODE TAKAKURA (DESA BERBEK KECAMATAN WARU SIDOARJO) - zuraidah, safrin; sujatmiko, bambang; bustamin, maulidyah octaviani (Jurnal Abadimas Adi Buana, 2019)
Waste has become a problem that is really worrying everywhere. If you pay close attention, there are indeed a number of factors that cause waste problems to become serious. First, population growth. Second, more and more instant food with plastic packaging. Third, the habit of littering, the habit of consuming instant food in packaging, to the habit of throwing garbage without sorting between organic and non-organic waste will damage the ecosystem. The same problem is also experienced by Berbek Village in Sidoarjo Regency, the problem of waste and flooding that is always faced by the city cannot only be the responsibility of the government, but the community as one of the producers of household waste should always help reduce the amount of waste. Thisneeds to provide an understanding to the community of environmental concerns, especially regarding household waste management and water conservation for the future based on water conservation. The results achieved from this activity are that the village community is aware of and understands the importance of a clean environment, there is no garbage scattered, puddles or floods can be reduced, and are able to practice independent waste management methods.